A Study on the Use of Milieu Teaching to Promote Overseas Marketers’ Communication Skills and Confidence in Language Learning - Jia, Simeng; Zhao, Xue (Frontiers in Psychology, 2022)
Language plays an extremely important role for people in terms of engaging in various learning activities. Due to the progress of network technologies, it is an immediate goal for enterprises to take a completely new development direction with the application of network technology. Nevertheless, they encounter many difficulties in carrying out overseas marketing, such as localization transformation, jet lag, lack of professional marketers, problems with sellers’ product quality, problems with customers’ credit checks, international payment problems, and logistics and delivery problems. These problems mainly result from the difference in language families.The current study was conducted as an experimental study with the participation of overseas marketers in Hebei Province. Milieu teaching was implemented with an experimental group and the traditional teaching was maintained in the control group for a 20-week (3 hours per week) experimental procedure. The research results revealed significantly positive effects of 1. milieu teaching on communication skills, 2. milieu teaching on language learning confidence, and 3. communication skills on language learning confidence. Based on the results it can be stated that the study is expected to help effectively enhance communication skills and language learning confidence of overseas marketers to achieve the goals of promoting oral expression and language-use skills.